Budaya Arab Dan Kearifan Lokal: Menyelusuri Nilai-Nilai Tradisional Dalam Masyarakat Modern - Ali Ridho; Febri Priyoyudanto (Student Research Journal, 2024)
Research aims to explore the interaction between Arab culture and local wisdom in Indonesia, particularly in preserving traditional values amidst modernization. This qualitative study employs in-depth interviews and participatory observation to collect data from Muslim community leaders in Jakarta. The findings indicate that traditional values such as mutual cooperation, respect for elders, and religiosity are still highly esteemed, albeit with varying interpretations. Muslim informants integrate religious teachings and ancestral traditions into their daily practices. They negotiate with modernity by adapting traditional values to be relevant to contemporary needs. In conclusion, traditional values persist in modern Muslim society in Indonesia through the selective integration of elements from Arab and local cultural heritage.